Identification of the biosynthetic gene cluster for the antibiotic polyketide L-155,175 in Streptomyces hygroscopicus - Kim, Eun Young; Han, Jae Woo; Lee, Jee Yeon; Kim, Beom Seok (Folia microbiologica, 2012)
The antibiotic L-155,175, a potent antiparasitic and antifungal compound, has an unusual structure involving 16-membered macrolides that contain a tetrahydropyran ring connected through a three-carbon linker chain. To identify the biosynthetic gene cluster for L-155,175, a genomic DNA library of Streptomyces hygroscopicus ATCC31955 was constructed and screened with a degenerate primer set designed from a conserved region of the ketosynthase (KS) domain. Sequence analysis of a fosmid clone, pEY1D8 (34 kb), revealed multiple open reading frames (ORFs) encoding type I polyketide synthase (PKS). To determine whether the cloned genes are involved in L-155,175 biosynthesis, a deletion mutant (1D8m) was generated by homologous recombination, in which the gene encoding the KS domain was substituted with an apramycin-resistance gene by PCR-targeted Streptomyces gene replacement. LC-MS analysis showed that L-155,175 production was completely abolished in the 1D8m strain, thereby proving that the cloned gene is responsible for L-155,175 biosynthesis. The sequencing of two other fosmid clones (pEY8B10 and pEY1C9) harboring overlapping sequences from pEY1D8 revealed a 60-kb DNA segment encoding six ORFs for type I PKS harboring 12 modules. The domain organization of the PKS modules encoded by PKS exactly matched the structure of L-155,175. This is the first report on the gene cluster involved in the biosynthesis of L-155,175.
Keywords: Macrolides; Open Reading Frames; Biosynthetic Pathways; DNA bakterií; polyketidy; genový knockout; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Polyketides; Anti-Infective Agents; antiinfekční látky; Gene Knockout Techniques; sekvenční analýza DNA; biosyntetické dráhy; DNA, Bacterial; otevřené čtecí rámce; makrolidy; genová knihovna; multigenová rodina; Multigene Family; Streptomyces; Gene Library